2014
DOI: 10.1038/ncomms6525
|View full text |Cite
|
Sign up to set email alerts
|

Singular localization of sodium channel β4 subunit in unmyelinated fibres and its role in the striatum

Abstract: Voltage-gated Na(+) channel β-subunits are multifunctional molecules that modulate Na(+) channel activity and regulate cell adhesion, migration and neurite outgrowth. β-subunits including β4 are known to be highly concentrated in the nodes of Ranvier and axon initial segments in myelinated axons. Here we show diffuse β4 localization in striatal projection fibres using transgenic mice that express fluorescent protein in those fibres. These axons are unmyelinated, forming large, inhibitory fibre bundles. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 56 publications
5
84
0
Order By: Relevance
“…For example, we recently reported that sodium channel beta 4 subunit (Navβ4) is a major determinant of resurgent currents in DRG neurons (3). Our results were consistent with Central Nervous System (CNS) studies, which proposed the C-terminal sequence of this subunit acts as an open channel blocker (2, 21, 39). In particular, a region of 20 amino acids within the cytoplasmic C-terminal region (known as the β4 peptide) is predicted to be key for Navβ4 positive regulation of fast resurgent currents (57, 75).…”
Section: Introductionsupporting
confidence: 92%
“…For example, we recently reported that sodium channel beta 4 subunit (Navβ4) is a major determinant of resurgent currents in DRG neurons (3). Our results were consistent with Central Nervous System (CNS) studies, which proposed the C-terminal sequence of this subunit acts as an open channel blocker (2, 21, 39). In particular, a region of 20 amino acids within the cytoplasmic C-terminal region (known as the β4 peptide) is predicted to be key for Navβ4 positive regulation of fast resurgent currents (57, 75).…”
Section: Introductionsupporting
confidence: 92%
“…Global deletion of Navβ4, however, may affect motor performance through other pathways. It has been reported, for example (Miyazaki et al, 2014), that loss of Navβ4 disrupts firing in medium spiny neurons of the striatum, which is also involved in action selection and motor control.…”
Section: Discussionmentioning
confidence: 99%
“…compound, frozen by dry ice-cooled ethanol and then cut using cryostat. 15-μm-thick sections were autoclaved for antigen retrieval and immunostained as described previously40. We used following primary antibodies for immunostaining: rabbit polyclonal anti-human C-terminal AMCase at 1:1,000 dilution and goat polyclonal anti-Pepsin C at 1:500 dilutions.…”
Section: Methodsmentioning
confidence: 99%